Polyacrylonitrile (PAN) nanofiber mats for mushroom mycelium growth investigations and formation of mycelium-reinforced nanocomposites - Trabelsi, Marah; Mamun, Al; Klöcker, Michaela; Brockhagen, Bennet; Kinzel, Franziska; Kapanadze, Dato; Sabantina, Lilia (Journal of Engineered Fibers and Fabrics)
Mycelium-bound composites are new environmentally friendly, cost-effective and sustainable materials, enable energy-saving bio-composite fabrication, and provide an alternative to synthetic materials. Current research on mycelium-based composites reports on relatively coarse material compositions such as rice husks, cotton residues, sawdust, leaves and bio-waste, etc. According to research, very few publications report on mycelium-reinforced composites with the use of nanomaterials and this topic is under-researched and this study helps to fill this gap. The focus of this study deals with the preparation of mycelium-reinforced nanocomposites including nanofiber mats and the investigation of the different nanofiber mat morphologies on the growth of fungal mycelium. The mycelium macrofibers from Pleurotus ostreatus fungi were grown on polyacrylonitrile (PAN) nanofiber mats. Different morphologies of nanofiber mats such as fibrous and non-fibrous membrane areas or a mixture of both were used for mycelial growth with an additional nutrient. Moreover, mycelium/PAN nanocomposites were oxidative stabilized and carbonized and mycelium retains its morphology. For faster color differentiation between mycelium and nanofibers, PAN nanofiber mats were dyed in a one-step process by adding dye powder to the electrospinning solution as an additional tool. No significant differences in mycelial growth and morphology were observed regarding the different nanofiber mat types and the use of dye. These mycelium-reinforced nanocomposites are promising for many applications such as medicine and biotechnology, air and water purification and filtration, vertical farming, architecture, etc., and enable energy-saving bio-composite fabrication.